Utilization of microalgae and accumulation of lipids for biodiesel production from grey-water in Makurdi area of Benue State, Nigeria - Igomu, B. C.; Ogbonna, I. O.; Gberikon, G. M. (Direct Research Journal of Biology and Biotechnology, 2024)
This study was conducted to investigate the utilization of some microalgae for simultaneous remediation of grey-water and accumulation of lipid for biodiesel production. Isolation was achieved by serial dilutions of the algal suspension in Bold’s Basal medium (BBM). The algal DNA was isolated using cetyltrimethyl ammonium bromide (CTAB). Morphological analysis established that the shape, size, and colour of various isolates matched those of members of the genus Chlorella.Four pure algal cultures were isolated from the grey-water channel and designated Chlorella lewinii KU220 JNI1, Chlorella vulgaris. NEIST JNI3, Chlorella lewinii KU217 JNI6, and Chlorella spp. NC JNI8. The Chlorella strains were confirmed to the genus level by ITS2 rDNA as shown by BLAST. The FT-IR characterization of the biodiesel indicated peak region at 1745 cm–1 Chlorella spp. were isolated from grey-water which produced biodiesel with high yield per algae biomass 50 g of Chlorella spp. biomass generated 5.1 g of lipid which was converted to biodiesel from simple trans-esterification reaction. FT-IR spectrum revealed that Chlorella spp. lipids were converted tofatty acidmethyl ester (FAME) at 1745 cm-1 stretch, while the standard value for ester bond formation was obtained at 1744 cm-1 stretch. The physicochemical properties of the biodiesel produced from Chlorella spp. analyzed were all in accordance with the ASTM standard.